2004
DOI: 10.1073/pnas.0403620101
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of Nrf2 causes regenerative immune-mediated hemolytic anemia

Abstract: A basic leucine zipper transcription factor, NF-E2-related factor 2 (Nrf2), plays a critical role in the cellular defense mechanism by mediating a coordinate up-regulation of antioxidant responsive element-driven detoxification and antioxidant genes. Here, we report that targeted disruption of Nrf2 causes regenerative immune-mediated hemolytic anemia due to increased sequestration of damaged erythrocytes. Splenomegaly and spleen toxicity in Nrf2 ؊/؊ mice raised a possibility of hemolytic anemia and splenic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 31 publications
5
95
0
1
Order By: Relevance
“…Nrf2 Ϫ/Ϫ mice, lacking the ability to induce ARE-driven gene expression, are more susceptible to a variety of toxic insults in vivo (35,38,59,60). Furthermore, Nrf2 Ϫ/Ϫ mice are known to spontaneously develop hemolytic anemia and a lupus-like syndrome relatively late in life (52,61,62). The wide array of tissues affected by Nrf2 deficiency suggests a strong role in general cellular protection.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 Ϫ/Ϫ mice, lacking the ability to induce ARE-driven gene expression, are more susceptible to a variety of toxic insults in vivo (35,38,59,60). Furthermore, Nrf2 Ϫ/Ϫ mice are known to spontaneously develop hemolytic anemia and a lupus-like syndrome relatively late in life (52,61,62). The wide array of tissues affected by Nrf2 deficiency suggests a strong role in general cellular protection.…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, Chan et al [24] showed that NRF2 is not essential in developmental processes but later this have been challenged [25][26][27]. SKN-1, the Caenorhabditis elegans ortholog of NRF2, is known to be important in the mesoderm and endoderm formation [28].…”
Section: Functional Analysis Of the Nrf2 Interactomementioning
confidence: 99%
“…The IgG bound to RBCs was assessed for RBC that had been washed with PBS three times followed by incubation with FITC-conjugated rabbit anti-mouse IgG (100 times dilution; Dako) [23].…”
Section: Flow Cytometry Analyses Of Ros and Bound Igg To Rbcsmentioning
confidence: 99%